A method for express estimation of the octane number of gasoline using a portable spectroimpedance meter and statistical analysis methods - Mamykin, A. V.; Kukla, A. L.; Maistrenko, A. S.; Matzas, E. P.; Matvienko, L. M. (Technology and design in electronic equipment, 2017)
The authors propose a method for determination of the electro-physical characteristics of electrical insulating liquids on the example of different types of gasoline. The method is based on the spectral impedance measurements of a capacitor electrochemical cell filled with the liquid under study. The application of sinusoidal test voltage in the frequency range of 0,1—10 Hz provides more accurate measurements in comparison with known traditional methods. A portable device for measuring total electrical resistance (impedance) of dielectric liquids was designed and constructed. An approach for express estimation of octane number of automobile gasoline using spectroimpedance measurements and statistical multi variation methods of data analysis has been proposed and tested.